CpPosNeg: A positive‐negative selection strategy allowing multiple cycles of marker‐free engineering of the Chlamydomonas plastome. Issue 10 (12th May 2022) - Jackson, Harry O.; Taunt, Henry N.; Mordaka, Paweł M.; Kumari, Sujata; Smith, Alison G; Purton, Saul
Abstract: The chloroplast represents an attractive compartment for light‐driven biosynthesis of recombinant products, and advanced synthetic biology tools are available for engineering the chloroplast genome ( = plastome) of several algal and plant species. However, producing commercial lines will likely require several plastome manipulations. This presents issues with respect to selectable markers, since there are a limited number available, they can be used only once in a serial engineering strategy, and it is undesirable to retain marker genes for antibiotic resistance in the final transplastome. To address these problems, we have designed a rapid iterative selection system, known as CpPosNeg, for the green microalga Chlamydomonas reinhardtii that allows creation of marker‐free transformants starting from wild‐type strains. The system employs a dual marker encoding a fusion protein of E. coli aminoglycoside adenyltransferase (AadA: conferring spectinomycin resistance) and a variant of E. coli cytosine deaminase (CodA: conferring sensitivity to 5‐fluorocytosine). Initial selection on spectinomycin allows stable transformants to be established and driven to homoplasmy. Subsequent selection on 5‐fluorocytosine results in rapid loss of the dual marker through intramolecular recombination between the 3′UTR of the marker and the 3′UTR of the introduced transgene. We demonstrate the versatility of the CpPosNeg system by serial introduction of reporter genes into the plastome. Graphical Abstract and Lay Summary: The CpPosNeg system allows for the generation of marker‐free chloroplast transformants using a dual marker in a two‐step process. Positive selection conferred by aadA is used to generate initial transformants and drive them to homoplasmy (R1). Negative selection conferred by codA is then used to drive the loss of the marker via intramolecular recombination (R2). The system can be used iteratively for multiple rounds of transformation.